Disaster Control of Roof Falling in Deep Coal Mine Roadway Subjected to High Abutment Pressure. (12th January 2021) - Zhang, Shizhong; Fan, Gangwei; Chai, Ling; Li, Qizhen; Chen, Mingwei; Luo, Tao; Ren, Shang
Abstract : The roof falling accident is a serious threat to the lives of miners in deep coal mining, especially when the coal mine is more than 1000 meters deep. In regard to the 5306 coalface in the Tangkou coal mine, Shandong, China, the depth of coal seam is 992.8 m and the stress concentration coefficient of the roadway surrounding rock is 3.33. This leads to a serious deformation of the roadway roof, thereby producing a high risk of the roof falling disaster. In this pursuit, based on the mechanical analysis of roadway roof subjected to a high abutment pressure, the mathematical expressions of the setting load and movable column length of supports were introduced. Furthermore, the stability control mechanism of the roadway roof was analyzed and the optimized support parameters of supports are provided. The results showed that the longtime effective support of the roadway roof required the strength and deformation coupling of supports and anchored surrounding rock. The support length of the belt roadway should be at least 57.7 m, with 0-30 m away from the coalface supported by hydraulic supports and 32-57.7 m supported by single props. In addition, the maximum setting load and movable column length of hydraulic supports were 21.67 MPa and 280.3 mm and 12.44 MPa and 177.1 mm for single props, respectively. By applying the optimized support parameters of supports to the belt roadway of the 5306 coalface, the effective control of the roadway roof and the disaster control of roof falling were realized.